Centralized Management For Effective Public Diplomacy: Case of Hasabara - V. V. Kabernik (Vestnik MGIMO-Universiteta)
The following paper is the first in the series dedicated to review and analysis of cases of centralization of public diplomacy affairs management for better promoting the agenda of the state. Introduction focuses on the erosion of traditional diplomatic practices shifting towards the stark attraction of soft power and public diplomacy. The evolution of modern public diplomacy in new media and the ways of its practical implementation reviewed, stating the raising power of non-government actors and mass media with their greater influence developing political agenda. The shift is analyzed on temporal basis bearing in mind inception of web 2.0 happening almost simultaneously with theoretical basis of soft power and the role of public diplomacy in propagating it. The case outlined in the first part reviews the evolution of Israeli's Hasbara - public diplomacy apparatus implemented in Jewish State. This evolution demonstrates the shift from decentralized management and coordination paradigm towards structured complex of measures led by government bodies. The sources and reasons for such a shift are being analyzed while national specifics for public diplomacy coordination is outlined. Results of the study underline the deficiencies of the chosen centralization paradigm via government bodies' control. The approach is being compared with the current practices implemented in Russia, outlining the best practices and mistakes to avoid that could be deducted from Israeli experience.